2011
DOI: 10.1159/000322454
|View full text |Cite
|
Sign up to set email alerts
|

How Impulsivity Relates to Compulsive Buying and the Burden Perceived by Caregivers after Moderate-to-Severe Traumatic Brain Injury

Abstract: Background: Impulsivity is a core feature in patients with traumatic brain injury (TBI). The aim of the study is to investigate how a specific dimension of impulsivity, namely urgency (the tendency to act rashly when distressed), might shed new light on the aetiology of compulsive buying proneness in patients with TBI and to explore how urgency and compulsive buying relate to the burden perceived by the caregivers. Sampling and Methods: Caregivers of 74 patients with TBI were given 3 questionnaires in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 61 publications
1
16
0
3
Order By: Relevance
“…Consequently, the first objective of our study was to replicate in an independent sample previous results that demonstrated an increase in urgency, lack of premeditation, and lack of perseverance in patients with moderate to severe TBI when retrospectively compared with the preinjury condition (Rochat et al, , 2011. Second, we aimed to compare patients with TBI and matched healthy controls on two inhibition mechanisms highlighted by Friedman and Miyake (2004), namely, inhibition of prepotent response and resistance to proactive interference.…”
Section: Introductionmentioning
confidence: 95%
“…Consequently, the first objective of our study was to replicate in an independent sample previous results that demonstrated an increase in urgency, lack of premeditation, and lack of perseverance in patients with moderate to severe TBI when retrospectively compared with the preinjury condition (Rochat et al, , 2011. Second, we aimed to compare patients with TBI and matched healthy controls on two inhibition mechanisms highlighted by Friedman and Miyake (2004), namely, inhibition of prepotent response and resistance to proactive interference.…”
Section: Introductionmentioning
confidence: 95%
“…On the basis of a factorial analysis performed on the data of 400 students who were administered several impulsivity assessments tools, they identified four dimensions of impulsivity: urgency (the tendency to experience strong reactions, frequently under conditions of negative affects), the lack of premeditation (the difficulty to think and reflect on the consequences of an act before engaging in that act), lack of perseverance (the difficulty to remain focused on a task that may be boring or difficult) and sensation seeking (the tendency to enjoy and pursue activities that are exciting and openness to trying new experiences). This multidimensional model of impulsivity has recently been confirmed in a sample of patients with TBI with a short form of the UPPS Impulsive Behaviour Scale, which was specifically designed by Rochat et al [23][24][25] to assess impulsivity changes after TBI. This scale includes 16 items (4 items per dimension) with a pre-and post-TBI evaluation for each item in order to evaluate impulsivity changes since the head injury.…”
Section: Manifestations Of Impulsivitymentioning
confidence: 85%
“…Regarding the motivational aspect of impulsivity, several studies have highlighted significant links between sensation-seeking and reward sensitivity. Besides, these four impulsivity dimensions have been related to different behavioral disorders and/or psychopathological states [24,30]. Indeed, Rochat et al [24] recently reported significant correlations between the urgency dimension of impulsivity and a tendency to compulsive buying in a group of 74 patients with moderate to severe TBI.…”
Section: Manifestations Of Impulsivitymentioning
confidence: 99%
See 1 more Smart Citation
“…4.4). Impulsivity has also been linked to a sense of urgency and compulsive buying after traumatic brain injury (Rochat et al 2011). The phenomenon of the "disconnection between knowing and doing" is also relevant, as the loved one can verbalize, yet not execute a Table 11.8 Group treatment for longer-term practical worries…”
Section: Group Treatment To Cope With Longer-term Practical Worriesmentioning
confidence: 99%